Use of Septal Cartilage in Rhinoplasty to Correct Nasal Deformity After Unilateral Cleft Lip and Palate Surgery [Corrigendum] - Nguyen HL; Hoang MP; Nguyen VM; Tran TT; Le VS (Dove Medical Press, 2023)
Nguyen HL, Hoang MP, Nguyen VM, Tran TT, Le VS. Clin Cosmet Investig Dent. 2022;14:131–140 The authors wish to advise that the study reported in the published article was previously described in the Vietnamese publication: Hoàng Minh Phương, Lê Văn Sơn (2016). Đánh giá kết quả tạo hình biến dạng mũi bằng sụn vách ngăn ở bệnh nhân sau tạo hình khe hở môi - vòm miệng một bên. Tạp chí Y học Việt nam, 447,149-152 (Print version only). The author lists are different between the two versions because the English version was written independently of the previous Vietnamese publication and contained updated information.